A Scoping Review of Virtual Focus Group Methods Used in Rehabilitation Sciences. (1st August 2021) - Tran, Benjamin; Rafinejad-Farahani, Bahar; Moodie, Sheila; O'Hagan, Robin; Glista, Danielle
Virtual methods for conducting focus group studies are increasingly being used in many fields, including rehabilitation sciences. This is partly due to the current pandemic, and the need for social distancing, however, may also relate to factors such as convenience and practicality. Virtual research methods enable investigators to collect data at a distance from the participant(s) through the use of technology-mediated data collection methods incorporating new tools and technologies. The aim of this scoping review was to identify, synthesize, and present current evidence related to the methods for conducting virtual focus groups. A comparison of asynchronous and synchronous data collection methods was conducted. The objectives, inclusion criteria, and scoping review methods were specified in advance and documented in a protocol. The 40 articles in this review included virtual focus group research conducted in rehabilitation sciences including data collection conducted using both synchronous (22.5%) and asynchronous (77.5%) models and using a defined moderation method. Three modes of focus group discussion were reported including email, chat-based, and videoconferencing; these were facilitated through the various technology platforms reported in the review. Reported barriers and facilitators to conducting virtual focus group research were extracted and summarized. Commonly reported facilitators to virtual focus group research included the ability to recruit participants from diverse geographical locations and the participants' ability to engage at times convenient to them. Both computer literacy and access to technology were reported as common barriers. This review highlighted the need for further research and guidance around virtual focus groups conducted using face-to-face synchronous methods and with younger participants groups.